2016
DOI: 10.1016/j.neuroscience.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix hyaluronan signals via its CD44 receptor in the increased responsiveness to mechanical stimulation

Abstract: We propose that the extracellular matrix signals CD44, a hyaluronan receptor, to increase the responsiveness to mechanical stimulation. We report that intradermal injection of hyaluronidase induces mechanical hyperalgesia, that is inhibited by co-administration of a CD44 receptor antagonist, A5G27. The intradermal injection of low (LMWH) but not high (HMWH) molecular weight hyaluronan also induces mechanical hyperalgesia, an effect that was attenuated by the pretreatment with HMWH or A5G27. Pretreatment with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 108 publications
3
47
1
Order By: Relevance
“…We have previously found that the chondrogenic effect of HA on ADSCs is mainly through CD44, one of the HA receptors . Moreover, signalling via CD44 has been shown to increase responses to mechanical stimulation through protein kinase A (PKA) and Src . On the basis of previous studies and the results presented here, we suggest that the difference in matrix stiffness of 3 D HA hydrogels may affect the chondrogenesis of ADSCs via CD44 signalling.…”
Section: Discussionsupporting
confidence: 66%
“…We have previously found that the chondrogenic effect of HA on ADSCs is mainly through CD44, one of the HA receptors . Moreover, signalling via CD44 has been shown to increase responses to mechanical stimulation through protein kinase A (PKA) and Src . On the basis of previous studies and the results presented here, we suggest that the difference in matrix stiffness of 3 D HA hydrogels may affect the chondrogenesis of ADSCs via CD44 signalling.…”
Section: Discussionsupporting
confidence: 66%
“…For example, currently the most commonly used endpoint in skeletal pain behaviors is skin hypersensitivity as assessed by von Frey (mechanical testing) or the Hargreaves method (thermal) [2; 20; 51; 67]. While it may be peripheral and/or central sensitization [15; 21; 29; 50; 60; 64] that is driving this skeletal injury induced skin hypersensitivity, from the perspective of a patient with skeletal pain due to osteoarthritis or TKA/THA, evoked skin hyperalgesia is rarely the major pain complaint [18; 55; 62]. Rather the major complaint of patients with orthopedic surgery pain is the spontaneous pain that arises upon use of the bone/joint that interferes with their quality of life, functional status, and ability to participate in the needed physical therapy and rehabilitation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Direct interactions between HA and the transient receptor potential cation channel subfamily V member 1 (TrpV1; also known as the capsaicin receptor) expressed by dorsal root ganglion neurons decreased receptor activation and sensitization, leading to reduced responses to capsaicin and heat [ 70 ]. Loss of HA through hyaluronidase administration to the footpad of rats increased pain sensitivity in a CD44 dependent manner [ 71 ], suggesting that HA can also influence neuronal activity at sensory neuron endings. HA has also been found to modulate the activities of CNS neurons.…”
Section: Hyaluronic Acid Acts As Both a Structural Element Of The mentioning
confidence: 99%